2011
DOI: 10.1084/jem.20101059
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF influences mouse skeletal muscle development and regeneration by stimulating myoblast proliferation

Abstract: Granulocyte colony-stimulating factor and its receptor are needed for skeletal muscle development and injury-induced regeneration in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 61 publications
2
86
1
Order By: Relevance
“…These cells get committed to myogenic differentiation and fuse with existing muscle fibers. [56][57][58][59][60][61] In vivo skeletal muscle growth is identified by hypertrophy (increase in fiber size) and hyperplasia (increase in fiber number), [62][63][64] while in vitro myogenic differentiation can be quantified by fusion index (ratio of fused nucleus) and area (hypertrophy) of myotubes. 42,43 In addition, maintenance of myotubes is influenced by signals of skeletal muscle protein Figure 1 sF-induced differentiation in hskMcs.…”
Section: Discussionmentioning
confidence: 99%
“…These cells get committed to myogenic differentiation and fuse with existing muscle fibers. [56][57][58][59][60][61] In vivo skeletal muscle growth is identified by hypertrophy (increase in fiber size) and hyperplasia (increase in fiber number), [62][63][64] while in vitro myogenic differentiation can be quantified by fusion index (ratio of fused nucleus) and area (hypertrophy) of myotubes. 42,43 In addition, maintenance of myotubes is influenced by signals of skeletal muscle protein Figure 1 sF-induced differentiation in hskMcs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in addition to myogenic cells, inflammatory cells, which are recruited to the damaged area, provide an important contribution to muscle regeneration. Indeed, recent studies have shown that factors expressed during the inflammatory process can influence skeletal muscle regeneration by stimulating satellite cell survival and/or proliferation (38,39). For example, recent data provided evidence that infiltrating inflammatory cell-derived granulocyte colony-stimulating factor enhances myoblast proliferation and facilitates skeletal muscle regeneration, thereby underscoring the importance of inflammation-mediated induction of muscle regeneration (39).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have shown that factors expressed during the inflammatory process can influence skeletal muscle regeneration by stimulating satellite cell survival and/or proliferation (38,39). For example, recent data provided evidence that infiltrating inflammatory cell-derived granulocyte colony-stimulating factor enhances myoblast proliferation and facilitates skeletal muscle regeneration, thereby underscoring the importance of inflammation-mediated induction of muscle regeneration (39). Conditional Cripto inactivation in adult satellite cells allowed us to unmask the cellular contribution of Cripto in vivo and provide previously undescribed evidence for a functional role of this protein during muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…3h,i), suggesting that genetic G-CSFR signal ablation negatively affects the population of PAX7 þ cells in vivo. We previously showed that G-CSF apparently activates JNK and p38 signalling in cultured myoblasts 9 . Therefore, we examined whether these pathways are active in activated SCs.…”
Section: G-csf Increases Scs Via the G-csf-g-csfr Axismentioning
confidence: 97%
“…In our previous screen for myocyte differentiationpromoting factors 6,7 , we noted markedly elevated expression of granulocyte colony-stimulating factor receptor (G-CSFR, encoded by csf3r) in the developing somite 8 . Furthermore, G-CSFR was transiently expressed in regenerating myocytes of adult injured skeletal muscle, and extrinsic G-CSF supported short-term muscle regeneration in cardiotoxin-induced skeletal muscle injury 9 and crush injury 10 . However, although we found high G-CSFR expression in regenerating immature myocytes, whether G-CSFR would be expressed in SCs and whether G-CSF signalling would affect the SC population in skeletal muscle remain unclear.…”
mentioning
confidence: 96%